Human Paramyxovirus Infections Induce T Cells That Cross-React with Zoonotic Henipaviruses - Rory D. de Vries (American Society for Microbiology, 2020)
ABSTRACT Humans are infected with paramyxoviruses of different genera early in life, which induce cytotoxic T cells that may recognize conserved epitopes. This raises the question of whether cross-reactive T cells induced by antecedent paramyxovirus infections provide partial protection against highly lethal zoonotic Nipah virus infections. By characterizing a measles virus-specific but paramyxovirus cross-reactive human T cell clone, we discovered a highly conserved HLA-B*1501-restricted T cell epitope in the fusion protein. Using peptides, tetramers, and single cell sorting, we isolated a parainfluenza virus-specific T cell clone from a healthy adult and showed that both clones cleared Nipah virus-infected cells. We identified multiple conserved hot spots in paramyxovirus proteomes that contain other potentially cross-reactive epitopes. Our data suggest that, depending on HLA haplotype and history of paramyxovirus exposures, humans may have cross-reactive T cells that provide protection against Nipah virus. The effect of preferential boosting of these cross-reactive epitopes needs to be further studied in light of paramyxovirus vaccination studies. IMPORTANCE Humans encounter multiple paramyxoviruses early in life. This study shows that infection with common paramyxoviruses can induce T cells cross-reactive with the highly pathogenic Nipah virus. This demonstrates that the combination of paramyxovirus infection history and HLA haplotype affects immunity to phylogenetically related zoonotic paramyxoviruses.